EDUCATION SUPERVISION IN THE CREDIBILITY COMPETENCY OF PROFESSIONAL TEACHER - Syamsul Arif (Yayasan Literasi Kita Indonesia, 2021)
Every activity of the school organization must be supervised by the principal. This is important because without supervision, all school program activities will not be successful. In this case, if there are deviations, it cannot be detected early and in detail. The role of the principal in this case is very important, in other words that success in carrying out supervision is largely determined by the skills of the supervisor. Supervision comes from the words super and vision which means to see and review from above or view and judge from above what is done by superiors on activities, creativity, and bottom performance.